Is the "Preferred" Color Temperature Transferable from Near-Vision to Ambient Home Lighting? An Exploratory Study with People Who Have Central Visual Field Loss. (November 2020) - Vincent, Claude; Bourassa, Julie; Cimon, Nathalie; Verville, Paule; Dumont, Frédéric
Introduction: The literature supports the importance of adequate lighting for people with visual impairments, but little is known regarding ambient color temperature at home, and the evaluation process is not standardized. Thus, this study aimed to test a method for evaluating the preferred ambient color temperature, established with a near-vision assessment in clinic, and by using standardized tools to evaluate the effects at home for people with central visual field loss. Methods: An exploratory quasi-experimental study was conducted with three interventions and six observation times. A convenience sample of eight women and two men with central visual field loss, aged 64–91 years with visual acuity between 6/21 (20/69) and 6/48 (20/158), was recruited. Two certified low vision therapists realized evaluations with Minnesota Low-Vision Reading Test, International Reading Speed Texts, a Visual Comfort Scale, a Digital Light Meter LX1330B, and Home Environment Lighting Assessment. The LuxIQ and various illuminated magnifiers were used for clinical interventions. Home lighting interventions were individualized and aimed to apply participants' preferred color temperature in a selected room. Results: The use of the LuxIQ and illuminated magnifiers showed positive effects in near-vision for all participants by increasing reading speed and visual comfort. Home lighting interventions in participants' kitchen ( n = 4), living room ( n = 4), or office ( n = 2) also had beneficial effects on their visual comfort and ability to perform activities of daily living. The choice of preferred color temperature was transferable from near-vision to ambient lighting for all participants but one and varied widely. Discussion: Innovative preliminary data support the importance of ambient color temperature for people with visual impairments and suggest an efficient standardized evaluation method. Further research is needed to obtain statistically significant empirical evidence in this field.Implications for practitioners: It could be beneficial for low vision therapists to evaluate the individual ambient color temperature preferences of people with visual impairments by using standardized tools.